PENGEMBANGAN SUMBERDAYA APARATUR DALAM MENINGKATKAN PRESTASI KERJA PADA BADAN PENGELOLAAN KEUANGAN DAN ASET DAERAH KABUPATEN KUTAI BARAT - Reni Syaftien (Magister Administrasi Publik FISIP Universitas Mulawarman, 2019)
The purpose of this study is to describe and analyze the resource pengembangkan apparatus in improving job performance in Financial Management Board and the Regional Asset (BPKAD) and explain the factors supporting and inhibiting. This study focused on BPKD efforts in developing the ability of its employees. This study is qualitative descriptive. Data was obtained through interviews, observation and document, and then analyzed using an interactive model. The results of the study explained that the development of human resources in BPKAD been done through delivery of education and training of employees, increase employee competence, work and award mutation or motivation. The results of these efforts is quite good, but not optimal in improving employee job performance BPKAD Kutai Barat.Keyword: development, human resources, job performance